Self‐Regulatory Resources Power the Reflective System: Evidence From Five Domains - Vohs, Kathleen D. (Journal of Consumer Psychology, 2006)
In this commentary, I focus on the deficiencies in the reflective‐impulsive model (RIM) by Strack, Werth, and Deutsch (2006) in terms of understanding the mechanics of the reflective system. Strack et al. outlined the cognitive architecture of the consumer with the RIM but failed to specify how its most impressive feature, the reflective system, is powered. Drawing on the literature on self‐regulation (as a reconceptualization of RIM incompatibility), I argue that self‐regulatory resources drive the reflective system. Research from 5 domains—overeating among dieters, impulsive spending, logical thinking, making choices, and subjective perceptions of duration—supports this hypothesis.